The Role Of Cell Block In Routine Cytology And Immunohistochemical Study Of Serous Effusions - عيسى, رنا; داود , علي; العباس, زينه (Latakia University Journal -Medical Sciences Series, 2021)
Objective : to shed the light on the essential role of cell block in detecting malignancy in serous effusions with emphasising on the value of applying IHC when it's necessary. Materials and methods : 89 serous fluids of pleural effusion and ascites were collected over 6 months in our laboratory. Each specimen was subjected to conventional smear examination and to cell block preparation using the easiest and cheapest techniques. The results of the two methods were compared for detecting malignancy in serous effusions using observational analytical study. IHC was done on cell block when it was required. Results : The cell block increased the yield of detecting malignancy by 24 % comparing to the conventional smear. In our study the accuracy of cell block in detecting malignancy was 100 % while it was 76% in the conventional smear. Conclusion : The cell block plays an important role in detecting malignancy in serous effusions as it has a high cellularity compared to the conventional smear and it provides the possibility of performing IHC, special stains and molecular studies. It also gives the advantage of diagnosing unknown primary tumors and prevents using invasive diagnostic methods. Its good benefits can always be achieved even if it is prepared by using the easiest and cheapest techniques.